Induced reproduction and early development histology of Oscar Astronotus ocellatus (Agassiz, 1831) (2015)
Oscar (Astronotus ocellatus) is an important fish from the Amazon Basin that has great potential for fish farming, human consumption, sport fishing and fish keeping. This study aimed to evaluate the effect of two hormonal treatments on the induction of artificial reproduction in broodstock and to describe the histological development of embryos and larvae. Broodstocks were selected and induced using two different hormones: (i) extract of carp pituitary (ECP); and (ii) synthetic human chorionic gonadotropin (hCG). Spawnings were transferred to hatcheries, collected at pre-established times, processed and analysed by histology. Astronotus ocellatus did not respond well to induced reproduction. From 16 couples of breeding fish, only five out of the eight females released oocytes after the hormonal action time, three with hCG and two with ECP; just one male responded positively to hCG. Oscar eggs were oval, and semi-adhesive, the yolk contained granules, and egg diameter was approximately 1.65 ± 0.057 to 1.98 ± 0.038 mm. Development from the initial collection (IC) point until the total absorption of the yolk lasted 315 h, at an average temperature of 27.45 ± 2.13°C. Several events marked embryonic and larval development, including the formation of the optic cup, forebrain, otic vesicle and cephalic divisions. The newly hatched larvae had non-pigmented eyes, and a closed mouth and anus, as well as the presence of adhesive glands on the head. Larval development was characterized by formation of the heart, liver, gaseous bladder, gills, pronephros, brain, fins and also the digestive tract. These results provide important information for the rearing and reproduction of A. ocellatus. Copyright © Cambridge University Press 2013.